2019
DOI: 10.3390/su11195151
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Tourism Involvement and Place Attachment in Determining Residents’ Attitudes Toward Industrial Heritage Tourism in a Resource-Exhausted City in China

Abstract: An in-depth discussion of place attachment in the relationship between residents’ perceived tourism impacts and their support for tourism is still lacking. The predictor of tourism involvement in this relationship has also been underestimated and little attention has been paid to industrial heritage tourism in relation to residents’ attitudes toward tourism development. To fill this gap, we extend upon the existing studies of residents’ attitudes toward tourism with place attachment (both place identity and pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 94 publications
3
63
0
2
Order By: Relevance
“…In addition, the attitudes of residents are also positive in regard to some non-economic variables, which has already been registered in some previous research [24]. All these results are in accordance with numerous studies that have noticed an important link between observed benefits to the host population and support for tourism activities [38,41,44,49], thereby supporting hypothesis H1 and suggesting that positive perceptions about various tourism impacts lead to support for the further development of sustainable tourism.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In addition, the attitudes of residents are also positive in regard to some non-economic variables, which has already been registered in some previous research [24]. All these results are in accordance with numerous studies that have noticed an important link between observed benefits to the host population and support for tourism activities [38,41,44,49], thereby supporting hypothesis H1 and suggesting that positive perceptions about various tourism impacts lead to support for the further development of sustainable tourism.…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, if they feel that expansion of tourism would produce more costs than benefits, they are likely to oppose this development [15,[34][35][36][37]. Based on social exchange principles, numerous studies worldwide have detected an important link between observed benefits to the host population and support for tourism activities [38][39][40][41]. At the same time, it was found that the perceived costs negatively affect this kind of community support [38,39,42].…”
Section: Theoretical Background and Research Hypothesismentioning
confidence: 99%
“…Our results also corroborate the hypotheses posed by a number of earlier studies based on the theory of social exchange, which indicated that the more positive the economic, socio-cultural, and environmental consequences for local residents, the greater their readiness to support tourism development, since they consider that this tourist activity will contribute, in general, to improving their community. Conversely, a greater perception of the negative impacts of tourism leads to lower levels of support [69,86]. The culture of wine and its use through wine tourism experiences in Gaia therefore offer growing potential for tourism, thanks to the strong support shown by the local community.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the confidence interval of correlations (correlation coefficient ± 2× standard error) between BEH and EA1 (0.805 ± 2 × 0.041 = 0.877, 0.723); EA1 and EA2 (0.848 ± 2 × 0.038 = 0.924, 0.772); BEH and PD (0.759 ± 2 × 0.039 = 0.837,0.681); EA1 and PD (0.807 ± 2 × 0.037 = 0.881, 0.733); EA2 and PD (0.754 ± 2 × 0.043 = 0.840,0.668); and PD and PI (0.852 ± 2 × 0.030 = 0.912, 0.792) did not include the cutoff criterion 1.0, indicating a tenable discriminant validity. Note: SE Boot: the standardized errors (SE) were estimated by the bootstrapping maximum likelihood approach with 10,000 resamples in AMOS; the factor loadings of all indicators were significant (p < 0.001) as determined by the two-tailed 95% bias-corrected percentile method [87]; SMC = squared multiple correlation.…”
Section: Measurement Model: First-order Cfamentioning
confidence: 99%
“…Furthermore, the AVE value of place attachment (PA) was 0.852, well exceeding 0.5, supporting convergent validity. Note: SE Boot: the standardized errors (SE) were estimated by the bootstrapping maximum likelihood approach with 10,000 resamples in AMOS; the factor loadings of all indicators were significant (p < 0.001) as determined by the two-tailed 95% bias-corrected percentile method [87]; SMC = squared multiple correlation.…”
Section: Measurement Model: Second-order Cfamentioning
confidence: 99%